STRENGTH AND USES OF FRESH AND SALT WATER ICE. - Hansen,Ralph; Linell,Kenneth (1949)
The report is an analysis of the structural usefulness of fresh and salt water ice in the Arctic. The uses of both sea ice and fresh water ice as an aid to transportation are given. Ranges of ice strength and tests results are given in tables. (Author)